Pengaruh kualitas produk,kualitas pelayanan,store atmosphere dan customer experience terhadap kepuasan pelanggan di sepasi coffee - Saputra, Rizkianto Adi; Uripi, Cahyaningtyas Ria; Pahlevi, Akbar (Parsimonia - Jurnal Ekonomi dan Bisnis, 2025)
The rapid growth of the coffee shop industry in Purwokerto has intensified competition, prompting business owners to understand the factors that influence customer satisfaction in order to maintain their existence. This study aims to analyze the influence of product quality, service quality, store atmosphere, and customer experience on customer satisfaction at Sepasi Coffee. A quantitative approach was used, employing a survey method by distributing questionnaires to 110 respondents selected through snowball sampling. The data were analyzed using multiple linear regression with the help of SPSS 25. The results of the study indicate that all four independent variables simultaneously have a significant effect on customer satisfaction. Partially, product quality, service quality, store atmosphere, and customer experience each have a positive and significant impact on customer satisfaction. These findings suggest that implementing strategies focused on improving product quality, responsive service, a comfortable store atmosphere, and a pleasant customer experience can enhance consumer satisfaction. The results also support the Stimulus-Organism-Response (SOR) theory, which explains that stimuli from the store environment affect customer emotions, leading to satisfaction behavior. Therefore, it is recommended that Sepasi Coffee’s management maintain and further develop the elements that positively contribute to the overall customer experience.